Anticipation of Normal Asthenia Syndrome of Faith in Congregation: Implementation of Psalm 4:1-9 - Rosmey Meriaty br. Sormin; Naomi Sirait; Andar Gunawan Pasaribu (The International Conference on Education, Social Sciences and Technology (ICESST), 2024)
The Asthenia Syndrome Normality (ASN) of Faith is a phenomenon of weakness and fatigue in the realm of faith. Normal faith asthenia syndrome can evolve into abnormal forms. The research method employed is qualitative, drawing from literature on asthenia. The proposed developmental model is the "Christ's face radiance" model. Anticipatory steps for ASN involve: "eyes" radiating to signify the activity of reading the word of God, "face" turning towards God, and "path" indicating the journey of life lived with faith and hope.